Discovery of allosteric SHP2 inhibitors through ensemble-based consensus molecular docking, endpoint and absolute binding free energy calculations. (January 2023) - Jama, Maryam; Ahmed, Marawan; Jutla, Anna; Wiethan, Carson; Kumar, Jitendra; Moon, Tae Chul; West, Frederick; Overduin, Michael; Barakat, Khaled H.
Abstract: SHP2 (Src homology-2 domain-containing protein tyrosine phosphatase-2) is a cytoplasmic protein -tyrosine phosphatase encoded by the gene PTPN11. It plays a crucial role in regulating cell growth and differentiation. Specifically, SHP2 is an oncoprotein associated with developmental pathologies and several different cancer types, including gastric, leukemia and breast cancer and is of great therapeutic interest. Given these roles, current research efforts have focused on developing SHP2 inhibitors. Allosteric SHP2 inhibitors have been shown to be more selective and pharmacologically appealing compared to competitive catalytic inhibitors targeting SHP2. Nevertheless, there remains a need for novel allosteric inhibitor scaffolds targeting SHP2 to develop compounds with improved selectivity, cell permeability, and bioavailability. Towards this goal, this study applied various computational tools to screen over 6 million compounds against the allosteric site within SHP2. The top-ranked hits from our in-silico screening were validated using protein thermal shift and biolayer interferometry assays, revealing three potent compounds. Kinetic binding assays were employed to measure the binding affinities of the top-ranked compounds and demonstrated that they all bind to SHP2 with a nanomolar affinity. Hence the compounds and the computational workflow described herein provide an effective approach for identifying and designing a generation of improved allosteric inhibitors of SHP2. Highlights: SHP2 is a proto-oncogene that plays a crucial role in regulating cell growth. This study used in silico screening of 6 million compounds to identify SHP2 allosteric inhibitors. 26 top ranked hits were validated for their binding to SHP2 using protein thermal shift assay. 3 hits were further validated for their binding to SHP2 using a biolayer interferometry assay. These compounds were shown to bind SHP2 with a nanomolar affinity.